Clerks III [videorecording (Blu-Ray)] - Smith, Kevin, 1970-; Smith, Kevin, 1970-; O'Halloran, Brian, 1969-; Anderson, Jeff, 1970-; Fehrman, Trevor; Zajur, Austin, 1995-; Ghigliotti, Marilyn; Smith, Jennifer Schwalbach, 1970-; Mewes, Jason, 1974-; Dawson, Rosario (Lionsgate, 2022)
Dante, Elias, and Jay and Silent Bob are enlisted by Randal after his heart attack to make a movie about the convenience store that started it all.